Mobsters, unions, and feds : the Mafia and the American labor movement - Jacobs, James B. (New York University Press, 2006)
Nowhere in the world has organized crime infiltrated the labor movement as effectively as in the United States. Yet the government, the AFL-CIO, and the civil liberties community all but ignored the situation for most of the twentieth century. Since 1975, however, the FBI, Department of Justice, and the federal judiciary have relentlessly battled against labor racketeering, even in some of the nation's most powerful unions. Mobsters, Unions, and Feds is the first book to document organized crime's exploitation of organized labor and the massive federal cleanup effort. A renowned criminologist who for twenty years has been assessing the government's attack on the Mafia, James B. Jacobs explains how Cosa Nostra families first gained a foothold in the labor movement, then consolidated their power through patronage, fraud, and violence and finally used this power to become part of the political and economic power structure of Twentieth century urban America. Since FBI Director J. Edgar Hoover's death in 1972, federal law enforcement has aggressively investigated and prosecuted labor racketeers, as well as utilized the civil remedies provided for by the Racketeer Influenced and Corrupt Organization (RICO) statute to impose long-term court-supervised remedial trusteeships on mobbed-up unions. There have been some impressive victories, including substantial progress toward liberating the four most racketeer-ridden national unions from the grip of organized crime, but victory cannot yet be claimed. The only book to investigate how the mob has exploited the American labor movement, Mobsters, Unions, and Feds is the most comprehensive study to date of how labor racketeering evolved and how the government has finally resolved to eradicate it.